EFFECT OF PROFITABILITY, LEVERAGE, INTEREST RATE, AND INFLATION ON FINANCIAL DISTRESS - Verra Theresia Nikodemus; Dian Primanita Oktasari (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
Financial Distress is a phenomenon that shows a downward trend in a company's financial performance and is an early stage before bankruptcy. This study aims to examine the effects of profitability, leverage, interest rates, and inflation on the possibility of financial distress in the property and real estate sub-sector companies listed on the IDX. The population in this study was the property and real estate sub-sector companies listed on the IDX for the 2010-2018 period, and the sample selection method used was a purposive sampling method and obtained a sample of 153 companies. The method of data analysis was performed using logistic regression analysis with the E-Views 9 program. The results of this study show that profitability and leverage affect financial distress, while interest rates and inflation do not affect financial distress.